2021
DOI: 10.3389/fcell.2021.634056
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Analyses Reveals ZNF124 as a Critical Regulator in Highly Aggressive Medulloblastomas

Abstract: Medulloblastoma (MB) is the most common malignant pediatric brain tumor, however, the mechanisms underlying tumorigenesis in different MB subgroups remain incompletely understood. Although previous studies of MB predisposition have been conducted in tertiary referral centers primarily in Caucasian cohorts, it is not unclear clear whether there exist population-specific genetic alterations in MBs. In this study, we investigated the contribution of genomic and transcriptomic alterations to the risk of malignant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The fusion we report in this work has not been described in other works analyzing the transcriptional landscape of medulloblastoma so far [ 14 , 16 ]. The landscape of gene fusions in medulloblastoma is very heterogeneous with a low recurrence of the same fusion in different patients.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…The fusion we report in this work has not been described in other works analyzing the transcriptional landscape of medulloblastoma so far [ 14 , 16 ]. The landscape of gene fusions in medulloblastoma is very heterogeneous with a low recurrence of the same fusion in different patients.…”
Section: Discussionmentioning
confidence: 86%
“…Although immunotherapeutic approaches for medulloblastoma patients such as cancer vaccines, natural killer cells and CAR T cells are promising [ 44 ], one of the major limitations in treating medulloblastoma with immunotherapy is the low immunogenicity and mutational load. It is interesting to note that few reported medulloblastoma-specific fusion peptides, such as MLLT6–MRPL45, LCLAT1–ERBB4, ASAP1–WD4HV1 and PTEN–THAP9 [ 2 , 14 , 15 ] have similar immunogenic potential to the EPC2–GULP1 fusion peptide SAEEITLTI. Therefore, future studies are needed to determine whether medulloblastoma patients with EPC2-GULP1 or other fusions have a higher response rate to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regulatory mechanisms that control MYC activity and amplification for tumorigenesis in highly aggressive MYCdriven MB have remained incompletely understood. By integrating the transcriptomic and genomic profiles from our newly diagnosed and publicly available MB cohorts 5,6,25,33 , we found that CTDNEP1 mutations, which present predominantly in MYC-driven MBs, define a specific subset of aggressive MB tumors. In contrast to many mouse models of MYC-driven G3 MB, which require MYC overexpression and additional loss of p53 function 22,23 , here we demonstrate that ablation of a single gene, Ctdnep1, is sufficient to trigger MYC amplification and genomic instability, and promote malignant transformation of cerebellar NPCs into MYC-driven MB tumors.…”
Section: Nuclear Envelope Phosphatase Ctdnep1 Functions As a Novel Potent Tumor Suppressor In Highly Aggressive Mbsmentioning
confidence: 99%